2012
DOI: 10.1177/0731684412455955
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanoparticle weight fraction on morphology and thermal properties of epoxy/TiO2 nanocomposite

Abstract: Titania nanoparticle dispersion and its effect on thermal properties of epoxy-based nanocomposite were examined by producing it via ultrasonic vibration process. Atomic force microscope images of the epoxy/TiO2 nanocomposite revealed a good dispersion of nanoparticle up to an optimum level of loading (10 wt%), which results in its improved glass transition temperature and thermal stability. But, a higher particle loading in epoxy reflects decrease in the glass transition temperature and thermal stability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 28 publications
0
38
0
5
Order By: Relevance
“…The observed properties of our nanocomposites were compared to epoxy/TiO 2 and epoxy/CNTs nanocomposites found in literature: some authors found improved T g , thermal stability and/or mechanical properties [39][40][41] while other report on a decrease in T g as well as thermal stability [42]. Multi wall CNT as well as TiO 2 decreased the T g , but the combination of titania and CNT into a hybrid structure reduces the decrease of T g [43].…”
Section: à2mentioning
confidence: 74%
“…The observed properties of our nanocomposites were compared to epoxy/TiO 2 and epoxy/CNTs nanocomposites found in literature: some authors found improved T g , thermal stability and/or mechanical properties [39][40][41] while other report on a decrease in T g as well as thermal stability [42]. Multi wall CNT as well as TiO 2 decreased the T g , but the combination of titania and CNT into a hybrid structure reduces the decrease of T g [43].…”
Section: à2mentioning
confidence: 74%
“…Metal oxides are often used as fillers to improve electrical, optical, photocatalytic properties of the polymers. Recently, researchers concentrated their attention on titanium dioxide as a filler for the obtaining of optically transparent epoxy composites with a controlled refractive index [1], high thermal stability [2], mechanical properties [3], etc.…”
Section: Introductionmentioning
confidence: 99%
“…But hardly any work has been reported so far claiming the cluster free dispersion of MWCNTs in epoxy matrix by the ultrasonication process of mixing. However, it is reported that a simultaneous use of ultrasonic mixing and mechanical stirring, named as ultrasonic dual mixing (UDM) process, has the ability to produce practically cluster free nano particulate epoxy base composite having considerably improved physical and mechanical properties [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%